Probing the caveolin-1 P132L mutant: Critical insights into its oligomeric behavior and structure - Rieth, Monica D. (2012)
Caveolin-1 is the most important protein found in caveolae, which are cell surface invaginations of the plasma membrane that act as signaling platforms. A single point mutation in the transmembrane domain of caveolin-1 (proline 132 to leucine) has deleterious effects on caveolae formation in vivo, and has been implicated in various disease states, particularly aggressive breast cancers. Using a combination of gel filtration chromatography and analytical ultracentrifugation we found that a fully-functional construct of caveolin-1 (Cav1(62–178)) was a monomer in dodecylphosphocholine micelles. In contrast, the P132L mutant of Cav1(62–178) was dimeric. To explore the dimerization of the P132L mutant further, various truncated constructs (Cav1(82–178), Cav1(96–178), Cav1(62–136), Cav1(82–136), Cav1(96–136)) were prepared which revealed that oligomerization occurs in the transmembrane domain (residues 96–136) of caveolin-1. To characterize the mutant structurally, solution-state NMR experiments in lyso-myristoylphosphatidylglycerol were undertaken of the Cav1(96–136) P132L mutant. Chemical shift analysis revealed that compared to the wild type, helix 2 in the transmembrane domain was lengthened by four residues (wild type, residues 111 to 129; mutant, residues 111–133), which corresponds to an extra turn in helix 2 of the mutant. Lastly, point mutations at position 132 of Cav1(62–178) (P132A, P132I, P132V, P132G, P132W, P132F) revealed that no other hydrophobic amino acid can preserve the monomeric state of Cav1(62–178) which indicates that proline 132 is critical in supporting proper caveolin-1 behavior.